COMPARISON OF ANTINOCICEPTIVE EFFECTS OF ANALGESICS IN A CHEMICAL MODEL OF VISCERAL PAIN IN MICE - (:unkn) unknown (NOBEL ILAC, 2011)
Objective: There are several experimental methods to propose the efficacy of pharmacological agents to test nociception and analgesia. Acetic acid induced writhing test is an established method for studying visceral pain. The aim of this study is to compare efficacy and potency orders of tramadol, lornoxicam and paracetamol in a mice model and supply evidence for clinicians dealing with pre-emptive analgesia. Material and Method: Swiss albino mice were treated either with intraperitoneal physiological saline, tramadol (10.0 mg/kg, 5.0 mg/kg and 2.5 mg/kg), lornoxicam (0.65 mg/kg, 1.30 mg/kg and 2.60 mg/kg) or paracetamol (100 mg/kg, 50 mg/kg and 25 mg/kg) 5 min before inducing the writhing test. The mice received intraperitoneal 0.2 ml 3% acetic acid solution injections and the writhes were observed and recorded for 10 min. Percent maximum possible effects and median effective doses (ED50)were calculated and the efficacy order for the three agents were compared. Results: The efficacy order for the three agents was found as: Tramadol >= Lornoxicam > Paracetamol. Median effective doses (ED50) for the drugs were also calculated as 1.54 mg/kg, 5.20 mg/kg and 97.32 mg/kg for lornoxicam, tramadol and paracetamol respectively The potency order was observed as: Lornoxicam > Tramadol > Paracetamol. Conclusion: These results state that tramadol and lornoxicam have similar efficacy where pre-emptive role of paracetamol should be further questioned in a clinical setting.
Keywords: Pain; postoperative; nociception tests; analgesics; POSTOPERATIVE PAIN; TRAMADOL; LORNOXICAM; RAT; EFFICACY; MORPHINE; SURGERY